Dioscin Prevents the Mitochondrial Apoptosis and Attenuates Oxidative Stress in Cardiac H9c2 Cells - Qin, J.; Kang, Y.; Xu, Z.; Zang, C.; Fang, B.; Liu, X. (Drug Research, 2014)
To determine if dioscin protects cardiac cells from ischemia/reperfusion (I/R) injury by preventing apoptosis.Cardiac H9c2 cells were subjected to simulated I/R. Cell viability was evaluated by the methyl thiazolyl tetrazolium (MTT) colorimetry assay. Reactive oxygen species (ROS) were detected with dichlorodihydrofluorescein (DCF). Apoptosis was evaluated with flow cytometric assay. Rhodamine 123 (Rho123) was used to measure mitochondrial membrane potential (ΔΨm). ELISA was used to detect cytochrome c (Cyt-c) release from mitochondria to the cytosol. Bax and Bcl-2 mRNA expressions were measured with RT-PCR.Dioscin reduced cell death and lactate dehydrogenase (LDH) release in cells subjected to I/R. I/R induced apoptosis and cytochrome c release from mitochondria to the cytosol and this was prevented by dioscin. In support, dioscin decreased Bax but increased Bcl-2 mRNA expression. Dioscin prevented I/R induced dissipation of ΔΨm. Finally, dioscin increased superoxide dismutase (SOD) expression but reduced intracellular ROS and malondialdehyde (MDA) levels.Dioscin protects H9c2 cells from H/R injury by modulating the mitochondrial apoptotic pathway through attenuation of oxidative stress.
Keywords: dioscin; ischemia/reperfusion; oxidative stress; mitochondrion apoptotic pathway